Grãos de destilaria secos com solúveis (DDGS) na dieta de cabras Saanen em lactação - Pontes, Vanessa Pereira (2019)
The objective of this study was to determine the intake, digestibility of dry matter and nutrients, glucose and urea in the blood serum, to evaluate the lactation curve, body weight, milk yield and quality of Saanen goats, from calving to 120 days of lactation, fed with dried distillers grains with solubles (DDGS) replacing soybean meal. Fifteen lactating Saanen goats were used, distributed in a completely randomized design with three treatments and five repetitions. The diet was offered in the roughage: concentrate ratio 60:40, based on soybean meal (SM), DDGS, grounded corn and mineral-vitamin supplement, and corn silage as roughage. The treatments consisted of soybean meal (SM), soybean meal + dried distillers grains with solubles (SM + DDGS) and DDGS. Criteria for animal allocation in treatments were live weight and milk yield. The adaptation period to the diet was ten days before the expected calving date and the experiment was separated into four phases (1 to 30 days; 31 to 60 days; 61 to 90 days and 91 to 120 days in lactation). Intake and digestibility of dry matter and nutrients and total digestible nutrients were determined in all four periods. Fecal excretion was estimated using indigestible neutral detergent fiber as an internal indicator. For analysis of lactation curves, the nonlinear Wood model was assumed. Feed intake and milk production were recorded daily. There was a difference (P<0.05) among treatments for neutral detergent fiber intake from birth to 30 days of lactation, being higher for DDGS treatment. There was a difference (P<0.05) among treatments for dry matter digestibility, organic matter, ether extract, total carbohydrates and total digestible nutrients in the four lactation periods. The neutral detergent fiber digestibility presented a difference (P<0.05) among treatments, from delivery to 30 days, from 30 to 60 days of lactation and from 91 to 120 days of lactation. For non-fibrous carbohydrate digestibility, there was no difference (P>0.05) among treatments in the four periods. Among treatments, there was no difference (P>0.05) for body weight, as well as no difference in dry matter intake, daily milk production and milk quality. There was a difference (P <0.05) among the treatments SM, SM + DDGS and DDGS, presenting an average of 2.600, 2.490 and 1.820 for initial milk production (parameter a); from 0.214, 0.079, 0.194 for rate of increase of production to the peak of lactation (parameter b); from -0.003, -0.002 and -0.004 for rate of decline in yield after peak lactation (parameter c), respectively. There was a difference (P<0.05) among treatments for peak lactation, persistence and peak lactation day. Thus, soybean meal + dried distillers grains with solubles can be an alternative for feeding Saanen goats, from calving up to 120 days of lactation, as they maintain dry matter intake and digestibility, body weight, and total milk production and quality.